Zingiber zerumbet: A Scoping Review of its Medicinal Properties - Chan, Janice Sue Wen; Lim, Xin Yi; Japri, Norfarahana; Ahmad, Ida Farah; Tan, Terence Yew Chin (Planta Medica, 2023)
Zingiber zerumbet, a plant native to tropical and subtropical Asia, has a vast range of traditional uses and has been continuously studied for its medicinal properties. However, a systematic methodological approach in evidence synthesis on the plantʼs efficacy is lacking, and there is a need to elicit the current research status of this plant. This scoping review was conducted to systematically explore and collate the available scientific evidence on the efficacy of Z. zerumbet and its main phytoconstituents in various formulations, their biological mechanisms, and their safety. Results included 54 articles consisting of animal studies, while there were no published human studies. Only half of the included studies provided adequate reporting on the quality-related details of Z. zerumbet formulations. Identified pharmacological activities were analgesic, anti-inflammatory, anti-diabetic, anti-hyperlipidemic, anti-neoplastic, immunomodulatory, antioxidant, antipyretic, hepatoprotective, nephroprotective, gastroprotective, and locomotor-reducing activities. Notably, the ethanolic extract of Z. zerumbet was found to be well tolerated for up to 28 days. In conclusion, Z. zerumbet and zerumbone have various pharmacological effects, especially in analgesic and anti-inflammatory models. However, there is still a pressing need for comprehensive safety data to conduct clinical trials.
Keywords: Zingiberaceae; zerumbone; lempoyang; ginger; herbal medicine; phytomedicine